Electromagnetic wave model of hydrogen and helium distribution at the formation of the solar system - Andrieieva, O.L.; Tkachenko, V.I.; Tkachenko, G.A. (Problems of Atomic Science and Technology, 2023)
This paper considers the formation process of the protosolar hydrogen-helium cloud in chronological order. From the list of hypotheses about the solar system formation, the electromagnetic hypothesis of Alfvén was selected since it is based on the plasma state of the protosolar hydrogen-helium cloud. It presumably describes a supernova explosion and its contribution to the solar system formation. The spatial-temporal dynamics of changes in the density and velocity of ions in a cylindrical two-component hydrogen-helium plasma is described. It is shown that the motion velocities of two-type particles represent Benard cells oscillating with different periods. The proposed electromagnetic wave model was used to calculate the distribution of hydrogen and helium ions in the solar system at the beginning of its formation and after a supernova explosion. У хронологічній послідовності розглянуто процес формування протосонячної воднево-гелієвої хмари. Електромагнітна гіпотеза Альфвена була обрана зі списку гіпотез про формування Сонячної системи, оскільки в її основі лежить плазмовий стан воднево-гелієвої хмари. Описаний, ймовірно, вибух наднової та оцінений його внесок у формування Сонячної системи. Описано просторово-часову динаміку зміни і густини та швидкості іонів у циліндричній двокомпонентній воднево-гелієвій плазмі. Показано, що швидкості руху частинок сорту α є осцилюючими з різними періодами осередку Бенара. На основі запропонованої електромагнітної хвильової моделі проведено розрахунок розподілу іонів водню та гелію в Сонячній системі на початку її формування та після вибуху наднової.